Procreative autonomy, gender equality and right to life: the decision of the Inter-American Court of Human Rights in Artavia Murillo v. Costa Rica - Teresinha Teles Pires (Revista Direito GV)
Resumo The trial and the reasons adopted by Inter-American Court of Human Rights (IACtHR) in Artavia Murillo v. Costa Rica represent significant progress in protecting women’s procreative autonomy. The decision of the IACtHR revoked a decision of the Constitutional Chamber of Costa Rica that banned the use of In Vitro Fertilization (IVF) in the country. With this decision, the IACtHR not only clearly linked universal rights of freedom with procreative autonomy for women and men; the IACtHR also strongly reinforced an interpretation on the “right to life” that favors procreative autonomy. Moreover, the decision is remarkable to include a standard of equality in matters of procreative autonomy insofar as the IACtHR has held that women, because of negative gender stereotypes in society, have been greatly undermined by the decision of the Chamber of Costa Rica to ban IVF. Finally, as will be argued, courts may, in similar future cases, introduce the Convention of Belém do Pará in the analysis, considering that the elimination of IVF services (or other limitation of women’s procreative autonomy) can be seen as a form of violence against women’s moral integrity.